State of the art of dynamic value stream mapping in the manufacturing industry - Thulasi, M.; Faieza, A. A.; Azfanizam, A. S.; Leman, Z. (Universiti Malaysia Pahang, 2022)
Value stream mapping (VSM) is considered as an important tool in lean manufacturing that allows analysts to visualize the actual situation that happens in the production value stream. However, in high-variety and low-volume factories, conventional VSM which is more static in nature, unable to give real vision of the variability problems concerning production process. As such, the purpose of this paper is to review the role of VSM in a dynamic context which is more efficient in today`s complex and dynamic manufacturing system.This paper discusses the conventional VSM, its applications and limitations as well as how conventional VSM integrates with computer simulation to display more dynamic behavior. Both these conventional and dynamic VSM have their own benefits and drawbacks according to their applications in the manufacturing industry. As a conclusion, this paper shows that simulation applications can help to support VSM for companies that intend to transform to lean. This work is very useful for both scholars and companies to know how much an output can be produced within the predicted lead time before making physical changes to the system in order to save both money and time.